INTERNATIONAL CRIMINAL COURT - Sekuloski, Branko (European Scientific Journal, ESJ, 2013)
This paper contains the effort of the world civilization and needs of formation of permanent International criminal court. The paper describes establishing of the Rome Statute of the International Criminal Court and its ratification. Further in the paper, the structure of the Rome Statute is described. The author of the paper gives a summary about formation of the International criminal court, about the Rome Statute, its applying and certain obstructions that occurred in operation. Further, the organization and jurisdiction of the International criminal law is shown. In that direction, court composition and also the jurisdiction of the court are described. Within the jurisdiction of the court specifically are described the four hardest international crimes: genocide, crimes against humanity, war crimes, aggression and crime. Than the obligatory jurisdiction, complementary jurisdiction and the general principals of the international criminal law are described. Within the general principals of the international criminal law there are given the main principles: The principle of legality, Non bis in idem, Nullum crimen sine lege, Nulla poena sine lege, Non-Permissibility of retroactive act, The principle of personal criminal responsibility, Exclusion of jurisdiction against persons which are below the age of eighteen, Responsibility of commanders and other chiefs and other general principles. At the end of the paper, the penalties prescribed in the Rome Statute are given.